THE DEVELOPMENT OF A SUPPLEMENTARY COURSE IN CH16203 KNOWLEDGEABLE IN CHINESE CULTURAL TO DEVELOP CROSS CULTURE COMMUNICATION AND ANALYTICAL THINKING SKILL USING BRAIN BASED LEARNING WITH FLIPPED CLASSROOM FOR GRADE 6TH STUDENTS - kaewpetch, sirilak; Art-in , Sitthipon (Journal for Developing the Social and Community, 2023)
The purpose of this research were 1) to develop supplementary course in CH16203 Knowledgeable in Chinese Cultural to develop cross culture communication. To develop cross culture communication and critical thinking skills using a Brain-Based Learning with Flipped classroom of grade 6 students 2) develop students’ cross culture communication skills that have been an average score of not less than 70% and the number of students passing the criteria of 70% or more. 3) Develop students’ analytical thinking skill that have been learned to have an average score of not less than 70% and the number of students passing the criteria of 70% or more. The target group include school administrators, teachers, and grade 6 students. This research was research and development (R&D) The instruments used are 1) Additional course development needs questionnaire Ch16203 Knowledgeable in Chinese Cultural 2) Additional course Ch16203 Knowledgeable in Chinese Cultural 3) lesson plans 4) listening test for Cross-Cultural Communication Skills 5) Speaking skill Assessment form Cross-Cultural Communication 6) The test to measure the analytical thinking skills 7) a curriculum evaluation form The results of the research found that Results of the development of additional courses CH16203 Knowledge found that there was a high level of suitability, the mean (𝑥̅ = 4.28 , S.D. = 0.23). Students had average cross-cultural communication skills score of 22.27 representing 74.33 percent and there are 26 students who passed the criteria representing 86.67 percent, which is higher than the specified criteria. The students had scores on analytical thinking skills of 14.43, representing 72.12 percent, and there were 22 students who passed the criteria, representing 73.33%, which was higher than the set criteria.